2018
DOI: 10.1093/ijnp/pyy086
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoacylglycerol Lipase Reduces the Reinstatement of Methamphetamine-Seeking and Anxiety-Like Behaviors in Methamphetamine Self-Administered Rats

Abstract: BackgroundMethamphetamine is a highly addictive psychostimulant with reinforcing properties. Our laboratory previously found that Δ8-tetrahydrocannabinol, an exogenous cannabinoid, suppressed the reinstatement of methamphetamine-seeking behavior. The purpose of this study was to determine whether the elevation of endocannabinoids modulates the reinstatement of methamphetamine-seeking behavior and emotional changes in methamphetamine self-administered rats.MethodsRats were tested for the reinstatement of metham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This is in surprising contrast to the finding that CB1R antagonists also increase circulating ACTH and CORT ( Manzanares et al, 1999 ; Patel et al, 2004 ). To further complicate interpretation, chronic administration of the FAAH inhibitor URB597 during withdrawal suppressed pharmacological stressor-induced reinstatement of cocaine-seeking ( Chauvet et al, 2014 ), while acute URB597 administration did not ( Nawata et al, 2019 ). Nawata et al (2019) also report that systemic inhibition of monoacylglycerol lipase, the primary hydrolytic enzyme for 2-AG, using JZL184 reduced both anxiety and methamphetamine-seeking during footshock in a CB1R-dependent manner.…”
Section: Cannabinoid Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in surprising contrast to the finding that CB1R antagonists also increase circulating ACTH and CORT ( Manzanares et al, 1999 ; Patel et al, 2004 ). To further complicate interpretation, chronic administration of the FAAH inhibitor URB597 during withdrawal suppressed pharmacological stressor-induced reinstatement of cocaine-seeking ( Chauvet et al, 2014 ), while acute URB597 administration did not ( Nawata et al, 2019 ). Nawata et al (2019) also report that systemic inhibition of monoacylglycerol lipase, the primary hydrolytic enzyme for 2-AG, using JZL184 reduced both anxiety and methamphetamine-seeking during footshock in a CB1R-dependent manner.…”
Section: Cannabinoid Targetsmentioning
confidence: 99%
“…To further complicate interpretation, chronic administration of the FAAH inhibitor URB597 during withdrawal suppressed pharmacological stressor-induced reinstatement of cocaine-seeking ( Chauvet et al, 2014 ), while acute URB597 administration did not ( Nawata et al, 2019 ). Nawata et al (2019) also report that systemic inhibition of monoacylglycerol lipase, the primary hydrolytic enzyme for 2-AG, using JZL184 reduced both anxiety and methamphetamine-seeking during footshock in a CB1R-dependent manner. This seemingly contrasts with the findings by McReynolds et al (2018) , which showed that 2-AG synthesis in PrL-PFC was necessary for potentiated cocaine seeking following footshock.…”
Section: Cannabinoid Targetsmentioning
confidence: 99%
“…Besides this, Δ 8 -tetrahydrocannabinol, an exogenous cannabinoid, suppresses the reinstatement of METH-seeking behavior. An inhibitor of MAGL, JZL184, can reduce the cue- and stress-induced reinstatement of METH-seeking and anxiety-like behaviors in METH self-administered rats (Nawata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that low doses of CB1 receptor agonists produce anxiolytic-like effects whereas high doses produce anxiogenic-like effects 67,90 . It is possible that our dosing regimen mimicked the effects of a high dose of CB1 receptor agonists, but prior work showed anxiolytic-like effects of high JZL184 doses (32mg/kg and 40mg/kg i.p) during withdrawal from methamphetamine self-administration in rats 93 . Again, it must be remembered that we administered the drug days before anxiety-like behavior testing, which differs from most prior work.…”
Section: Discussionmentioning
confidence: 99%